Analysis of The Effect of Gross Domestic Product, Exchange Rate, and Inflation on Balance of Payments in Indonesia - Rinaldi, Muammar; Shinta Arida Hutagalung,; Muhammad Fitri Rahmadana, (Advances in Social Sciences Research Journal, 2019)
This study aims to analyze the effect of the short and long term gross domestic product, exchange rate, and inflation on Indonesia's balance of payments. The data used in this study are secondary data which is obtained indirectly with the period of 1995 to 2015. Data sources were obtained from Bank Indonesia and the Central Bureau of Statistics. The data collection method used in this study with the indirect method is documentation through recording or copying data from Bank Indonesia and the Central Bureau of Statistics. The analysis model used is Error Correction Mechanism (ECM). The results of this study indicate that the regression model of the Autoregressive Distributed Lag Model (ARDL) for the long term and Error Correction Model (ECM) regarding the effect of independent variables such as Interest Rates, Gross Domestic Product and Inflation Against the Dependent dependent variable in Indonesia, then it can some conclusions are presented, namely from several independent variables that are tried and included in the savings equation in Indonesia using the Autoregressive Distributed Lag Model (ARDL) for the long term and Error Correction Model (ECM) for the short term, namely the gross domestic product variable, the inflation rate, and exchange rate. In the long run there are 2 (two) significant variables, namely gross domestic product and the exchange rate. While inflation is not significant. For the short term, there is 1 (one) significant variable, namely the exchange rate. Thus, only exchange rate variables are significant in both the short and long term. With only 1 (one) significant independent variable both in the long term and short term, it can be concluded that the exchange rate in the long term and short term is the main determining factor that affects the Balance of Payments in Indonesia. In the long run, Independent variables such as Gross Domestic Product and the exchange rate on the dependent variable Balance of Payments in Indonesia have a significant effect on the dependent variable Balance of Payments. Whereas in the short run, the exchange rate variable has a significant effect, and for other independent variables such as the GDP variable and the inflation rate does not have a significant effect.